Protecting Children From Tobacco Smoke Exposure: A Randomized Controlled Trial of Project Zero Exposure. Issue 12 (22nd May 2021) - Rosen, Laura; Zucker, David; Guttman, Nurit; Brown, Nili; Bitan, Michal; Rule, Ana; Berkovitch, Mati; Myers, Vicki
Abstract: Introduction: Young children are vulnerable to harm from tobacco smoke exposure (TSE). This study assessed the effect of Project Zero Exposure—an intervention program designed to help parents protect children from TSE—on children's exposure. Methods: Randomized controlled trial of a home-based, theory-driven intervention. Parents of young children (<8 y) in families with a smoking parent were eligible. The intervention included feedback on child TSE (hair nicotine), and home air quality (PM2.5 ), with motivational interviewing. Families were randomized to: intervention group (IG, N = 69), regular control group (RCG, N = 70), or to a secondary enhanced control group, (ECG, N = 20). Child hair samples were taken at baseline and follow-up. We report on child TSE in the IG versus RCG at six months. Results: Most enrolled families completed the trial (IG: 98.6%[68/69], RCG: 97.1%[68/70]). Log hair nicotine (LHN [ng/mg]) decreased in both the IG (Baseline: –1.78 ± 1.91, Follow-up: –2.82 ± 1.87, p = .003) and RCG (Baseline: –1.79 ± 1.54, Follow-up: –2.85 ± 1.73, p = .002), but did not differ between groups at study end ( p = .635). Three of five parentally-reported outcomes showed improvement over time in the IG, and one in the RCG. Among IG participants, 90% found hair nicotine feedback useful. Conclusions: No difference between the intervention and control groups was found on the objective biomarker, LHN. Child TSE decreased during the trial in intervention and control groups. Trial participation, which included hair nicotine monitoring, may have contributed to decreasing exposure in both groups. Concurrent control group improvements may partially explain lack of proven intervention benefit. Biomarker monitoring warrants further investigation for reduction of child TSE. Implications: Project Zero Exposure is an intervention program designed to help parents protect their children from TSE. Results from the randomized controlled trial of the program showed no difference between groups at study end, but a clear and substantial reduction in child exposure to tobacco smoke from beginning to end of the trial, in both intervention and control groups. Biomarker monitoring, a key element of the trial, was used with all participants. Biomarker monitoring of child exposure to tobacco smoke may help parents become aware of their child's exposure and better protect them, and should be explored as a means to reduce child TSE. Clinical Trial Registration: NCT02867241